Zur Rekonstruktion der balto-slavischen Intonationen - Poliakovas, Olegas (Baltistica, 1996)
THE RECONSTRUCTION OF THE BALTO-SLAVIC INTONATIONSAccording to the classical doctrine, the Balto-Slavic intonations – the acute (a rising intonation) and the circumflex (a falling intonation) – were changed in Lithuanian, whereas they were preserved without any change in Old Prussian, Latvian and Slavic. Similar intonations to those in the last three languages are supposed to have existed in Ancient Greek, but it is impossible to compare these intonations directly. We must furthermore note that conclusions based on a comparison of the Lithuanian and the Ancient Greek intonations in auslaut have been applied without justification to the intonations in anlaut in the other three languages. The present article offers an overall structural analysis of the intonations in the Baltic (including Low Lithuanian) and Slavic languages. It shows that such phenomena as the retraction of stress, the reduction which takes place in final syllables and some other facts made it impossible for the original Balto-Slavic intonations to be preserved in the languages in which these processes took place – in Low Lithuanian, Old Prussian, Latvian and Slavic. On the contrary, these intonations are preserved in Standard (High) Lithuanian, which was not touched by the processes.
Keywords: akcentologija; intonacija; baltų-slavų